Hayekian Hurdles: Challenges to Cryptocurrency as a Viable Basis for a New Monetary Order - Luís Pedro Freitas; Jorge Cerdeira; Diogo Lourenço (Economies)
The rise of cryptocurrencies over the past decade has promised to challenge the dominance of fiat money systems and reshape monetary policy. However, recent developments, including market volatility and the collapse of key exchanges like FTX, have eroded public trust, raising skepticism of a feasible transition to a crypto-based monetary system. This paper explores why cryptocurrencies have not met the expectations of their proponents, particularly those who saw them as a step towards Friedrich Hayek’s vision for competitive currency issuance. While cryptocurrencies reflect some aspects of Hayek’s model, their instability—especially in Bitcoin-like assets—undermines their role as a reliable alternative to fiat money. The paper also considers how central bank independence and regulatory gaps further hinder the development of a robust cryptocurrency framework. Despite the continued relevance of Hayek’s ideas in today’s monetary landscape, the entrenched structures of modern central banks and the rise of Central Bank Digital Currencies suggest that a decentralised currency order remains unlikely in the near future.